Total antioxidant capacity and total oxidant status of synovial fluids in patients with temporomandibular joint pain and dysfunction - ALKAN, ALPER; Etoz, Osman A.; Akcay, Huseyin; Neselioglu, Salim; Erel, Ozcan; Alkan, Alper (My University, 2012)
Objectives The objective of this study was to investigate whether a relationship exists between total antioxidant capacity (TAC) and total oxidant status (TOS) of synovial fluids (SFs) of temporomandibular joint (TMJ) pain patients with pain and dysfunction.